Pharmacokinetic correlates of venlafaxine: associated adverse reactions - Schoretsanitēs, Geōrgios; Gründer, Gerhard (European archives of psychiatry and clinical neuroscience, 2019)
To address the potential correlation between plasma concentrations of venlafaxine (VEN), its active metabolite O-desmethylvenlafaxine (ODVEN) and the active moiety, AM, (ODVEN + VEN) and adverse drug reactions (ADR) in a large naturalistic sample of in- and outpatients. We compared plasma concentrations of VEN, ODVEN and AM and dose-adjusted (C/D) levels as well the ODVEN/VEN ratios between patients complaining ADRs, following the Udvalg for Kliniske Undersogelser side effect rating scales (UKU) (n = 114) and patients without ADRs (control group, n = 688) out of a naturalistic database. We also investigated potential pharmacokinetic correlates of the four UKU categories by comparing patients complaining ADRs with those who did not. Based on previous literature we applied different ODVEN/VEN ratio values as cut-offs to split our sample into two groups at a time and compare frequencies of ADRs between the groups. No differences for demographic and pharmacokinetic variables including plasma and C/D concentrations as well as ODVEN/VEN ratios were observed between study groups. Neither the comparisons between females and males nor between elderly and non-elderly patients revealed significant differences (p > 0.05 in all cases). No differences were also reported exploring the patients complaining ADRs from the 4 UKU categories separately. After applying various ODVEN/VEN cut-offs, groups did not display differences in frequencies of ADRs (p > 0.05 in all cases). Our findings do not demonstrate a direct link between venlafaxine metabolism measures and ADRs. Therefore, additional dimensions are needed to be considered in future trials aiming to disentangle the involved aspects of ADRs in patients receiving venlafaxine.